2003
DOI: 10.1300/j160v03n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Belonging in School as a Protective Factor Against Drug Abuse Among Native American Urban Adolescents

Abstract: This article presents the results of a study conducted with 243 Native American students who were part of a multi-ethnic sample of adolescents attending middle school in a large urban center in the Southwest region of the United States. Native adolescents who felt a stronger sense of belonging in their school were found to report a lower lifetime use of alcohol and cigarettes, lower cigarette and marijuana use in the previous month, lower frequency of current use of these substances, fewer substances ever used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 25 publications
2
28
0
1
Order By: Relevance
“…School belongingness is usually defined as the feeling of connectedness with the school community, and it is assumed to contribute to academic motivation constructs, such as engagement and self-efficacy which, in turn, improve academic achievement (Goodenow, 1993;Osterman, 2000;Furrer and Skinner, 2003;Kia-Keating and Ellis, 2007;Roseth et al, 2008). Perceiving school as a caring community has also been reported to be positively related to students' attitude towards schooling, educational aspirations, and respect and trust in teachers , as well as to act as a protective factor against delinquent behavior, substance abuse, and depression among students (Battistich and Hom, 1997;Anderman, 2002;Napoli et al, 2003). While the empirical research activity has slowed down somewhat over the last decade, there are conceptual issues that are worth further investigation because sense of belongingness has a strong cultural component, particularly in the school context.…”
mentioning
confidence: 99%
“…School belongingness is usually defined as the feeling of connectedness with the school community, and it is assumed to contribute to academic motivation constructs, such as engagement and self-efficacy which, in turn, improve academic achievement (Goodenow, 1993;Osterman, 2000;Furrer and Skinner, 2003;Kia-Keating and Ellis, 2007;Roseth et al, 2008). Perceiving school as a caring community has also been reported to be positively related to students' attitude towards schooling, educational aspirations, and respect and trust in teachers , as well as to act as a protective factor against delinquent behavior, substance abuse, and depression among students (Battistich and Hom, 1997;Anderman, 2002;Napoli et al, 2003). While the empirical research activity has slowed down somewhat over the last decade, there are conceptual issues that are worth further investigation because sense of belongingness has a strong cultural component, particularly in the school context.…”
mentioning
confidence: 99%
“…Other studies underscored the need for researchers to understand what it means to be a member of an ethnically distinct group before attempting to develop prevention messages for members of those groups (Marsiglia, Miles, Dustman, & Sills, 2002;Napoli, Marsiglia, & Kulis, 2003;Okamoto, Hurdle, & Marsiglia, 2002;Sheets, 2003). Because no evidence-based research had been done with, by, and for adolescents from nondominant groups (Gosin, Dustman, Drapeau, & Harthun, 2003;Schinke, Botvin, & Orlandi, 1991) at the time this project was undertaken, the so-called culturally neutral messages of universal substance abuse prevention efforts ignored the contributions and needs of those students (Holleran, 2003;Hurdle, Okamoto, & Miles, 2002;Marsiglia et al, 2001).…”
Section: Project Foundationsmentioning
confidence: 99%
“…Research with American Indian youth has found that environmental variables serve as both risk and protection. For example, a sense of belonging to school has been shown to provide protection from drug use for American Indian youth of the Southwest (Napoli, Marsiglia, & Kulis, 2003). Trotter, Rolf, and Baldwin (1997) found through ethnographic analysis of interviews with Diné (Navajo) youth that decisions to use drugs were situated within a relational context.…”
Section: Theoretical Underpinnings Of Ecological Assessmentmentioning
confidence: 99%
“…Nonetheless, research on Indigenous populations has found that higher levels of ethnic pride were related to lower levels of drug use (Austin, 2004). Additionally, Napoli et al (2003) found that Native youth who felt a stronger sense of belonging to school reported lower lifetime and monthly use of gateway drugs (i.e., cigarettes, alcohol, and marijuana) than other Native youth. This suggests that the educational context of American Indian youth may be particularly important in the etiology of their drug using behavior.…”
Section: Stage 1: Survey Data Analysismentioning
confidence: 99%